Anatomic Guideline for Approach to Lateral Thoraco-Lumbar Interbody Fusion. Issue 1 (April 2016) - Cho, Woojin
Summary: The decision making process for incision location during the course of lateral thoraco-lumbar interbody fusion (LLIF) at 857 levels was evaluated retrospectively, in an attempt to develop a clinically robust anatomic guideline. Introduction: The minimally invasive technique of LLIF has shown powerful segmental deformity correction, with excellent fusion rates and minimal morbidity. However, in certain settings, adequate lateral access to permit a proper working angle into the disc space may be difficult to achieve. The purpose of this investigation was to establish a clinically robust anatomic guideline for incision location, with respect to laterality and level. Methods: The operative reports and plain films of the thoraco-lumbar spine of 512 consecutive patients undergoing LLIF at our institute between 2009 and 2011 by the mini-open transpsoas method were reviewed. Results: Distribution of operative levels is depicted inTable 1 . Table 1 Level of approach: T11–12 and above: transthoracic approach. T12-L1: 10 th intercostal space (retropleural/retroperitoneal approach). L1–2: 11 th intercostal space (retropleural/retroperitoneal approach). L2–3: below 12 th rib (retroperitoneal approach). L3–4: midway between costal margin and iliac crest (retroperitoneal approach). L4–5: above iliac crest (retroperitoneal approach). L5-S1: not recommended, even when accessible. T9–10 1 T10–11 2 T11–12 3 T12-L1 8 L1–2 80 L2–3 214 L3–4 286 L4–5 262 L5-S1 1 Total 857 The primary determinant of laterality (side) of operative approach involving the L4–5 disk space was coronal angulation of the L4–5 disk space, as depicted on 15° up-tilt view. A secondary determinant of feasibility of accessing the L4–5 disk space is a line drawn through the center of the L4 vertebra, parallel to the inferior end plate of L4. Extension of this line cephalad to the ipsilateral iliac crest indicates that this level will be surgically accessible. In the absence of segmental coronal angulation, the symptomatic side was chosen. In the setting of regional scoliosis, the concavity was the preferred side of approach, as up to three levels can be reached through a single small incision. There were no instances of approach failure using the method outlined above. Conclusion: A clinically robust and worthwhile anatomic guideline to LLIF, with respect to level and laterality of incision placement, is presented.